Severity impact of a Vapour Cloud Explosion (VCE) – Liquefied Petroleum Gas (LPG) road tanker accident - Rashid, Z.A.; A. Fuad, M.F.I.; Alias, A.B.; Ahmad, M.A.; M. Arif, M. A.; Zainal, S.; Asuat, A.Y.; Jamaludin, Iqbal; Abdullah, A. (Academy of Sciences Malaysia, 2023)
An explosion accident from a road tanker while carrying hazardous materials can have a dangerous effect on road users and the surrounding area through which the road tanker passes. Based on the evidence of the accident case involving the road tanker reported, it shows that this accident case can cause death and destruction to the surrounding property. In Malaysia, several cases of accidents involving road tankers have also occurred. Among the methods used to determine the impact of a road tanker explosion is the use of the consequences analysis method. Currently, there is limited number of software that can be used to determine the impact of a road tanker explosion accident that carries explosive chemicals such as butadiene, Liquefied Petroleum Gas (LPG), etc. However, there are weaknesses in the display of the impact results plotted on the map. Where the impact of the explosion is only shown to the 3 main zones, namely building damage, serious injury, and glass breakage. In this paper, the enhanced contour profile method on the impact of an LPG road tanker explosion on human and structural damage is shown.